1989
DOI: 10.1016/0014-5793(89)80963-9
|View full text |Cite
|
Sign up to set email alerts
|

Membrane‐binding sites for acyl carrier protein in Escherichia coli

Abstract: We report that membrane vesicles of Escherichia coli contain protein-binding sites for acyl carder protein. Scatchard analysis of the binding indicates a dissociation constant around 0.35/tM and a maximum number of protein-binding sites around 50 pmol per mg of membrane protein. Binding is on the inner membrane while the outer membrane is devoid of binding sites. These results are consistent with the fact that some aeyl carder protein-dependent enzymes implicated in phospholipid-and membrane-derived oligosaceh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(21 reference statements)
0
2
1
Order By: Relevance
“…The proportion of S. erythraea ACP released into the supernatant was approximately equal to the proportion of E. coli ACP released. These results do not necessarily support the proposal (Van der Bosch et al, 1970;Bayan and Therisod, 1989) that ACP is associated with the cytoplasmic membrane, but they do indicate that the freeze-thaw method of releasing ACPs from E. coli cells may be of general applicability. In the first instance, the induced E. coli K38 (pGPI-2, pFEX-1) cells were thawed into buffer A that contained no DTT.…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…The proportion of S. erythraea ACP released into the supernatant was approximately equal to the proportion of E. coli ACP released. These results do not necessarily support the proposal (Van der Bosch et al, 1970;Bayan and Therisod, 1989) that ACP is associated with the cytoplasmic membrane, but they do indicate that the freeze-thaw method of releasing ACPs from E. coli cells may be of general applicability. In the first instance, the induced E. coli K38 (pGPI-2, pFEX-1) cells were thawed into buffer A that contained no DTT.…”
Section: Resultscontrasting
confidence: 67%
“…both thioredoxin and elongation factor Tu are associated with the inner surface of the cytoplasmic membrane Lunn and Pigiet, 1982). Since evidence has been reported that E. coli ACP is associated with the cytoplasmic membrane (Van der Bosch et al, 1970;Bayan and Therisod, 1989), it was thought that it too might be selectively released from E. coli by osmotic shock. Attempts to purify the S. erythraea ACP by osmotic-shock release into various concentrations of sucrose solutions (15-40 %, w/v) were unsuccessful.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, osmotically shocked cells have been shown to retain a small (8.5-kDa) soluble acyl carrier protein (9), thus seemingly contradicting our conclusion. However, this protein might be prevented from exiting cells by binding the plasma membrane (2,3). The other apparent contradiction is presented by a large EntF polypeptide (142 kDa) that was shown to be partially released upon osmotic shock (9).…”
Section: Discussionmentioning
confidence: 99%